Analysis of Alternative Energy Efficiency in the Economy of Uzbekistan - Kodirov Bahodir Tursunovich (Research Parks Publishers, 2022)
This article discusses the importance of the production of renewable alternative energy resources in our society. It is reported that Uzbekistan has unlimited opportunities for the production of solar and wind electricity, the needs for foreign and domestic investment in its production, and therefore the construction of RER (Renewable energy sources) production stations in the regions. In this regard, hydrogen, which is an environmentally friendly fuel, is also important. At a time when 50-60% of the energy produced in the energy system in developed countries is due to renewable energy sources, the fact that this figure is less than 5% in Uzbekistan means that this issue is extremely relevant.